Breast cancer subtype specific biochemical responses to radiation - Meksiarun, Phiranuphon; Aoki, Pedro H. B. [UNESP]; Van Nest, Samantha J.; Sobral-Filho, Regivaldo Gomes; Lum, Julian J.; Brolo, Alexandre G.; Jirasek, Andrew (Royal Society of Chemistry (RSC), 2018)
External beam radiotherapy is a common form of treatment for breast cancer. Among patients and across different breast cancer subtypes, the response to radiation is heterogeneous. Radiation-induced biochemical changes were examined by Raman spectroscopy using cell lines that represent a spectrum of human breast cancer. Principal component analysis (PCA) and partial least squares discriminant analysis (PLSDA) revealed unique Raman spectral features in the HER2 and Ki67 subtype. The changes in Raman spectral profiles to different doses of radiation (0-50 Gy) included variations in the levels of proteins, lipids, nucleic acids and glycogen. Importantly, the differences in radiation-induced changes on the normal breast epithelial cell line MCF10A could be discriminated within and across the various breast tumor cell lines. These results demonstrate a novel approach to uncover differences between breast cancer cell subtypes and surrounding normal tissues by their biochemical variations in response to radiation.